Microinvasive mitral valve repair with transapical mitral neochordae implantation - Bergonzoni, Emma; D’Onofrio, Augusto; Mastro, Florinda; Gerosa, Gino (Frontiers in Cardiovascular Medicine, 2023)
Microinvasive cardiac surgery includes procedures performed off-pump, on the beating heart, with limited or absent skin incision, and those that rely on live imaging techniques. Transapical off-pump beating heart neochordae implantation allows the repair of severe mitral valve regurgitation due to leaflet prolapse or flail with live three-dimensional echo guidance. This procedure has shown good results for up to 5 years and can be considered as a valid alternative to conventional surgery in selected patients with high prediction of success based on clinical and anatomical considerations. The aim of this review is to describe the devices, indications, patient screening process, clinical and echocardiographic results, and future perspectives of this procedure.